A Study on the Status and Health Conditions of Working Children in the West and South Districts of Tripura. - Neogi, Debasis and Dutta, Papiya (2011)
India is very familiar with the concept of ―Child labour‖ as it is a burning issue and a social curse to mankind. It is poverty which compels parents to send their children to work so as to earn money to run their family. Owing to their tender age, children can be exploited easily by the employer both in the hazardous and non-hazardous sector. The present paper analyses the status of child labour in two districts of Tripura in north-east India. The paper also tries to find out the impact of work on the health conditions of the working children. Sometimes, the children are assigned the task of looking after their family and younger ones where they are not earning directly, but help the other family members to earn money and as a result some of them have dropped out from studies, while others are pushed out of earning compulsion which ultimately affects the mental growth of the child.